Evaluation of a Brief Suicide Prevention Training Program for College Campuses. Issue 1 (2nd January 2020) - Zinzow, Heidi M.; Thompson, Martie P.; Fulmer, Crystal B.; Goree, Jennifer; Evinger, Leasa
Abstract : Suicide is the second leading cause of death in college students. While research indicates a positive impact of gatekeeper training programs on knowledge and attitudes, few have examined change in suicide prevention behaviors. The purpose of this study was to evaluate the effects of a brief suicide prevention training for college campuses on knowledge, self-efficacy to intervene, and gatekeeper behaviors. A longitudinal design was employed to examine changes from pretest to post-test and 3-month follow-up. Participants included 517 students, staff, and faculty who attended a 90-minute training and completed self-report surveys. The training included both didactic and experiential components. Repeated measures ANOVAs indicated that knowledge, self-efficacy to discuss suicide and to refer to resources, and gatekeeper behavior increased from pretest to post-test and follow-up. Students exhibited a greater increase in gatekeeper behaviors, in comparison to non-students. Large changes were observed on publicizing suicide prevention information and having informal conversations about suicide with students, and 76% had engaged in gatekeeper behavior at follow-up. Findings offer support for the potential efficacy of a brief prevention program, with promising effects on several suicide prevention behaviors. Declines on knowledge and self-efficacy from post-test to follow-up highlight the importance of booster sessions and complementary programming.